Blazing the trail: the institutional framework for dispute resolution in Malaysia’s Islamic finance industry - Oseni, Umar Aimhanosi; Ahmad, Abu Umar Faruq (International Shari'ah Research Academy for Islamic Finance (ISRA), 2012)
The dispute resolution framework in Islamic finance as practiced in most countries has proven to be inadequate, particularly in its application and interpretation of the Sharīah. Malaysia has consistently proven its prime position in blazing the trail in most legal and regulatory issues in the Islamic finance industry. It has recognised the increasing importance of the architectural aspects of the industry such as the need to establish the dispute resolution framework.